2014
DOI: 10.1007/s12663-014-0656-2
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case Report of Mucinous Cystadenoma with Immunohistochemical Analysis and Review of Literature

Abstract: Cystadenomas are rare salivary gland tumours characterised by prominent epithelium-lined papillary projections into the cystic spaces. A 37 year-old female, presented with a swelling on the right side of the hard palate. Clinically, the swelling was soft, fluctuant, sessile and non-tender measuring 2.5 9 2 cm in diameter. Excisional biopsy was performed. The histopathological and immunohistochemical features were characteristic of mucinous cystadenoma. There has been no recurrence over a 2-year follow up perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…3 In the present case, the swelling also developed as a painless small mass over the period of 3 years at the peri-auricular area, finally reaching the size of 5.5 cm. It has been documented that females are more commonly affected than males, especially in advanced age (>50 years), 7 but in the current case, the swelling developed in a male patient of 44 years old. Contrary results were obtained in a study performed by Perks et al, 8 who reported a case of cystadenoma (both mucinous and papillary components) in a 78-year-old male with a 3-month history of an asymptomatic palatal swelling.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…3 In the present case, the swelling also developed as a painless small mass over the period of 3 years at the peri-auricular area, finally reaching the size of 5.5 cm. It has been documented that females are more commonly affected than males, especially in advanced age (>50 years), 7 but in the current case, the swelling developed in a male patient of 44 years old. Contrary results were obtained in a study performed by Perks et al, 8 who reported a case of cystadenoma (both mucinous and papillary components) in a 78-year-old male with a 3-month history of an asymptomatic palatal swelling.…”
Section: Discussioncontrasting
confidence: 50%
“…A report from the Japanese population documented a slowly enlarging tumor, 10 mm in diameter, in the hard palate. 9 Another case published by Girotra et al 7 reported a non-tender swelling on the right side of the hard palate of a female patient. Yet another case reported a 2-year history of a slow-growing tumor in the left parotid gland but without any obvious clinical symptoms.…”
Section: Figure 3 Photomicrograph On Hande Staining (A)showing a Cyst...mentioning
confidence: 96%
See 1 more Smart Citation
“…Recurrence is seldom seen, with more tumors recurring in major salivary glands than in minor ones. Inadequate removal due to an incomplete capsule or tumor cell infiltration of the parotid gland is probably responsible for recurrence[13,18]. Although cystadenoma of the salivary gland is a benign tumor, postoperative malignant transformation has been reported[19].…”
Section: Discussionmentioning
confidence: 99%